2015
DOI: 10.1111/evj.12524
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal effect of a multi‐strain probiotic on the intestinal bacterial microbiota of neonatal foals

Abstract: There were limited effects of probiotic treatment on the bacterial microbiota of foals. The studied probiotic based on lactobacilli and bifidobacteria has a limited potential for therapeutic modification of the gastrointestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
1
21
0
4
Order By: Relevance
“…Besides, it had been reported that a kind of probiotics might contribute to improve bowel symptoms such as diarrhea or constipation by altering microbiota and insetinal flora. Thus, our Bs would be consistent with this concept [11][12][13].…”
Section: Discussionsupporting
confidence: 81%
“…Besides, it had been reported that a kind of probiotics might contribute to improve bowel symptoms such as diarrhea or constipation by altering microbiota and insetinal flora. Thus, our Bs would be consistent with this concept [11][12][13].…”
Section: Discussionsupporting
confidence: 81%
“…reuteri, Lactobacillus johnsonii and Bifidobacterium boum, regulated intestinal function and contributed to diarrhoea prevention in neonatal Thoroughbreds. However, other studies have shown that the introduction of live, beneficial micro-organisms orally into the animal gut yielded variable results, with limited potential for therapeutic modification of foals' gastrointestinal microbiota and even adverse effects noted, with animals becoming more likely to develop diarrhoea requiring veterinary intervention (Schoster et al 2015(Schoster et al , 2016. Data in the literature have also reported the use of LAB that induced an inflammatory response to immune adjuvants in influenza, polio, rotavirus and cholera vaccines (Paineau et al 2008;Zhang et al 2008;Davidson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Unabeling free access to grass and hay and overfeeding with rapidly fermenting carbohydrates exposes horses to colics or laminitis more then in open pasture conditions (Kronfeld and Harris, 1997). Due to its' sensitivity, specifics of equine gastrointestinal tract should be considered when choosing an appropriate probiotic preparation (Weese et al, 2004;Schoster et al, 2015b). In horses the treatment of the gastrointestinal tract by the recovery of microbiota may represent "the next frontier in equine gastroenterology" (Mullen et al, 2016).…”
Section: Probiotics In Equine Medicinementioning
confidence: 99%
“…Even though in vitro activity of this probiotic showed good results, there was no influence on Clostridial fecal shedding in this study. The following study by Schoster et al (2015b) included 38 foals from a previous study investigating the probiotics effects on the bacterial microbiota during and after administration. Insignificant differences in relative abundance of families and species in treated foals proved limited potential of the used probiotics for therapeutic modification of the gastrointestinal microbiota.…”
Section: Clinical Studies In Foalsmentioning
confidence: 99%